Electrochemical reduction and cathodic stripping voltammetric determination of clotrimazole - Pereira, F. C.; Stradiotto, N. R.; Zanoni, MVB (Soc Brasileira Quimica, 2001)
The reduction of clotrimazole at a mercury electrode, in phosphate buffer, pH>6, involves a reversible one-electron process. The electrochemical process presents a large contribution from adsorption effects. For the differential pulse polarographic determination the addition of Triton X-100 is recommended. Clotrimazole can be determined by cathodic stripping voltammetry at 50 ng mL(-1) level when pre-accumulated for 3 min at an accumulation potential of -0.20 V. The proposed method is applied successfully for the determination of clotrimazole in a commercial formulation.
Keywords: clotrimazole; cyclic voltammetry; differential pulse polarography; cathodic stripping voltammetry